(3EOGQI GdehGQO GdHTQjIs - (3MfG(B, (3fUQ Gddgs ((3YeGf(B:s (3OGQ RgQGf(B,s, 2002)
(3CHYGO hXjaI EOGQI GdYfUQ GdHTQj,GdJhXja aj GdefTBJ,JfejI Gdbhi GdYGedI,SjGSGJ GdJYhjVGJ hGdCLhQ hGdefGaY,EOGQI GdYdGbGJ GdUfGYjIs
Keywords: (3EOGQI GdCaQGOs; (3GdCLhQs